2017
DOI: 10.5009/gnl16001
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Complete Response and Recurrence after Transarterial Chemoembolization in Hepatocellular Carcinoma

Abstract: Background/AimsTo investigate the predictive factors for complete response (CR) and recurrence after CR in patients with hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE).MethodsAmong 691 newly diagnosed HCC patients, 287 were treated with TACE as a first therapy. We analyzed the predictive factors for CR, recurrence after CR, and overall survival (OS).ResultsEighty-one patients (28.2%) achieved CR after TACE, and recurrence after CR was detected in 35 patients (43.2%). In mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 28 publications
8
39
0
Order By: Relevance
“…The fi ndings of the present study demonstrated an inverse association between tumor number and DFS time following initial TACE. Consistent with the present study, several previous studies have identified tumor number as a predictor of intrahepatic recurrence following initial TACE for HCC (27)(28)(29)(30)(31). Recurrence following initial remission by TACE has been more often reported in patients with multinodular-type HCC and with portal vein thrombosis (32).…”
Section: Discussionsupporting
confidence: 79%
“…The fi ndings of the present study demonstrated an inverse association between tumor number and DFS time following initial TACE. Consistent with the present study, several previous studies have identified tumor number as a predictor of intrahepatic recurrence following initial TACE for HCC (27)(28)(29)(30)(31). Recurrence following initial remission by TACE has been more often reported in patients with multinodular-type HCC and with portal vein thrombosis (32).…”
Section: Discussionsupporting
confidence: 79%
“…While surgical resection and local ablative therapies are considered curative, recurrence rates approach 25%‐35% within the first year and 50%‐60% within 2 years . Further, up to 25%‐50% of patients in some studies received TACE, which is typically not curative and associated with a high risk of recurrence . Further, patients with high‐risk tumour characteristics (eg, multifocal HCC or elevated AFP) have higher recurrence rates than their counterparts; however, specific data regarding these risk factors and subgroup analyses were not reported in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al [25] reported that 28.2% of patients with various stages of HCC who underwent TACE showed a complete response after treatment. Another study showed that 6 months after treatment for BCLC stage B/C HCCs, the overall response rate was 12.50% in the sorafenib monotherapy group and 18.75% in the TACE + sorafenib group [26].…”
Section: Discussionmentioning
confidence: 99%